Quando avere un lavoro non basta a proteggere dalla povert&agrave - Chiara Saraceno (Firenze University Press, 2020)
Having a job is not always a guarantee against poverty, for oneself and one's family. This depends on the one hand on the level of income acquired through work, on the other hand on the worker$1 (Bs family situation. While a low income does not always lead to poverty in terms of consumption - if the worker$1 (Bs family is able to provide additional incomes - on the contrary, an average income may not be sufficient if it is the only one in a family compose by several members. Low or intermittent work incomes, on the one hand, and high incidence of single-income families on the other hand - especially if they count several children - are among the main causes of poverty despite a work income. Above all, the second phenomenon explains why Italy is among the European countries with a relatively high percentage of poor workers on a family basis, a condition which is also the cause of a high incidence of child poverty.s
Keywords: income and poverty; poor workers; child poverty